HUBUNGAN PERILAKU ORANG TUA DALAM PENGAMBILAN KEPUTUSAN DENGAN DERAJAT DENGUE HEMORRHAGIC FEVER PADA ANAK DI RUMAH SAKIT BHAKTI RAHAYU SURABAYA - Heris Santy, Wesiana; Arminah, Amiriah (Unusa Press, 2013)
The decision making which is not done promptly and correctly can result in death because the incidence rate of DHF increases 5% each year. The purpose of this study was to study the correlation between the parents’ behavior in making decision and the severity level of DHF in children at RS BRS. The method was analytical done by using a retrospective approach. The population involved all parents whose children suffering from DHF at RS BRS, totally 30 respondents in which 28  respondents were taken as the samples by using simple random sampling technique. The independent variable was the the parents’ behavior in  making decision, whereas the dependent variable was the severity level of DHF.  The data were taken by using questionnaires and analyzed by uisng Mann-Whitney test in which a = 0.05. The results showed that among 13 respondents who have made decisions promptly, almost entirely (84.6%) had DHF at level 1. While 15 respondents who took the decision late, nearly all (40%) had DHF at level 2. After Mann-Whitney test, the research obtained r = 0.005 and = 0.05, meaning that r <a, so that H0 was rejected, showing that there was a correlation between the parents’ behavior and decision-making with the severity level of DHF at RSBRS. It concluded that the late decision-making resulting in the increase of severity level of DHF. Therefore, the parents are expected to make decisions quickly when the children has a fever to medically detect the disease  immediately and the children immediately receive the appropriate actions